Service innovation as a social construction: The role of boundary objects. (September 2019) - Mele, Cristina; Sebastiani, Roberta; Corsaro, Daniela
This article advances a conceptualization of service innovation as socially constructed through resource integration and sensemaking. By developing this view, the current study goes beyond an outcome perspective, to include the collective nature of service innovation and the role of the social context in affecting the service innovation process. Actors enact and perform service innovation through two approaches, one that is more concerted and another that emerges in some way. Each approach is characterized by distinct resource integration processes, in which the boundary objects (artifacts, discourses, and places) play specific roles. They act as bridge-makers that connect actors, thereby fostering resource integration and shared meanings.